ANALISIS BERPIKIR KRITIS PESERTA DIDIK SMA PADA MATERI PEMANASAN GLOBAL MELALUI TES BERBASIS MASALAH - Lailatul Fajriati; Oka Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students' critical thinking skills on global warming through problem-based tests. The research method used was quantitative descriptive with class XI subjects selected through purposive sampling techniques involving 32 students from class XI 1. The research instrument is in the form of a set of problem-based tests developed based on Facione's critical thinking indicators which include interpretation, analysis, evaluation, inference, and explanation and is equipped with a non-test questionnaire as a support for the analysis. The results of the study show that the average achievement of critical thinking skills of SMAN 17 Surabaya students is at 49% in the "adequate" category which is considered still below average, it should be 61%-80% to be said to be "Good". This indicates the need for improvements in learning strategies that can train students to be more active in exploring, analyzing, and evaluating information critically. This research has a novelty that lies in the use of problem-based tests that integrate the phenomenon of global warming directly in a real-life context. This study provides a new picture of how problem-based instruments can reveal students' critical thinking patterns on actual environmental issues that are more authentic and considered more relevant to improve critical thinking skills in high school.